2020
DOI: 10.1002/esp.4850
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced hysteresis of suspended sediment transport in response to upstream damming: An example of the middle Yangtze River downstream of the Three Gorges Dam

Abstract: The peak in sediment transport in alluvial rivers generally lags behind the peak in discharge. It is thus not clear how the hysteresis in the sediment/discharge relationship may be impacted by damming, which can fundamentally alter the water and sediment regimes in the downstream reaches of the river. In this study, a total of 500 flood events in the Yichang–Chenglingji Reach (YCR) of the Middle Yangtze River immediately downstream of the Three Gorges Dam (TGD) are analysed to study the impacts of dam operatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…In general, Q peak is characterized by flood waves while SSC peak is associated with flow velocity (Lyu et al, 2020). As shown in Figure 14, in the near‐dam region (the Miaohe Station) almost all the flood events are characterized by “ SSC peak lagging behind Q peak ”.…”
Section: Resultsmentioning
confidence: 99%
“…In general, Q peak is characterized by flood waves while SSC peak is associated with flow velocity (Lyu et al, 2020). As shown in Figure 14, in the near‐dam region (the Miaohe Station) almost all the flood events are characterized by “ SSC peak lagging behind Q peak ”.…”
Section: Resultsmentioning
confidence: 99%
“…For a long time, the downstream channel was basically a dynamic balance of sediment before the impoundment of the TGR. Therefore, the long-term average annual sediment concentration corresponding to each discharge before impoundment can be approximated as the saturated sediment concentration under this flow (Lyu et al, 2020), as shown in Figure 5e. The ratio of the sediment concentration investigated in Table 1 and the saturated sediment concentration is approximately taken as the sediment saturation degree (ξ), as shown in Figure 5f.…”
Section: The Sediment Saturation Degreementioning
confidence: 99%
“…The jacking force is an interactive force in that the lakes create a backwater effect on the Yangtze River and in turn, the Yangtze River has a block effect on the outlet of lakes. The MYR is a predominately meandering channel with many floodplains, and a riverbed composition that tends toward finer grain sizes downstream (He et al., 2021; Lyu et al., 2020).…”
Section: Study Areamentioning
confidence: 99%